F.R. David : Correctional Facility. - Holder, Will; Gruijthuijzen, Krist; Sarif, Alma; Anastas, Rhea; Van den Abeele, Michael; Van den Brande, Kristien; Reinfurt, David; Mihaylova, Snejanka; Handley, Sarah; Mangelschoots, Lula; Reynolds, Alex; di Serego Alighieri, Andrea; et al. ([s.l.] : uh books with Kw Institute for Contemporary Art, 2020)
Gruijthuijsen, Krist ; Sarif, Alma ; Anastas, Rhea ; Van den Abeele, Michael ; Van den Brande, Kristien ; Reinfurt, David ; Mihaylova, Snejanka ; Handley, Sarah ; Mangelschoots, Lula ; Reynolds, Alex ; Alighieri , Andrea di Serego ; Singh, Nicola ; Snowden, Robert
boek